Exploring Perceptions of Social and Emotional Health in Socially Isolated Emerging Adults Who Accessed Residential Treatment. Issue 3 (2nd October 2017) - Givetash, Sonja; Head, Sarah; Frensch, Karen; Cameron, Gary; Preyde, Michèle
ABSTRACT: The current report is part of a larger study on the perceptions of emerging adults who accessed residential treatment during adolescence. Interviews with a subsample of participants who self-identified as socially isolated were analyzed to explore social development and emotional health. The findings of this study include three themes regarding social difficulties: problems trusting other people, general dislike of other people, and problems in social interactions. Concerns with emotional health such as difficulty managing symptoms of depression and anxiety were reported. The ongoing struggles perceived by socially isolated emerging adults contribute to previous research on the enduring symptoms of mental health disorder.